Byssinosis and serum IgE concentrations in textile workers in an Italian cotton mill - Petronio, L (1983)
ABSTRACT The relationship between serum concentrations of total IgE and byssinosis and other respiratory symptoms was evaluated in 352 textile workers (90 men, 262 women) at a cotton mill in Friuli-Venezia Giulia, Italy. The subjects were aged from 20 to 61 (mean 44) and the mean duration of employment was 20 years. One hundred and eight subjects (30·7%) were smokers. Only 2% had a positive history of atopy. A standardised questionnaire showed chronic bronchitis in 96 textile workers (27·3%) and byssinosis in 63 (17·9%). The prevalence of respiratory disorders was the same for men and women but was higher in the carding room than in other work areas. Total serum IgE concentrations (RIST, Phadebas) were analysed after log transformation. The geometric mean was 192·7 IU/ml, with no significant difference between the two sexes. This mean concentration of IgE is much higher than that reported internationally for non-atopic subjects, but similar to values found in the Italian population. The IgE concentrations of the workers in the main departments (carding, spinning, and weaving) showed no significant difference. The geometric means were not different in subsamples stratified according to respiratory diseases (cases of pure and cases of mixed forms of chronic bronchitis and byssinosis). A negative result was obtained when IgE concentrations of 289 subjects without byssinosis (¯x = 188·4 IU/ml) and 63 with byssinosis (¯x = 212·6 IU/ml) were compared; there was also no trend when the results were analysed by clinical grade of byssinosis. The same negative pattern occured when the serum IgE concentrations were examined in patients with byssinosis with different grades of chronic change in FEV(1). The results of this study support the hypothesis that there is no relationship between total serum IgE concentrations and byssinosis.